What happens to our amputees? The Darling Downs experience. (14th October 2020) - Vasudeva, Varun; Parr, Adam; Loch, Alan; Wall, Chris
Background: Major lower limb amputation is occasionally required in the management of end-stage pathology where other treatment options have failed. The primary aim of this study was to determine the 30-day and 1-year mortality rates of patients undergoing nontraumatic major lower limb amputation. Secondary aims were to investigate risk factors for poor outcomes, incidence of previous minor amputation, and the rate of subsequent major amputation. Methods: All nontraumatic, major lower limb amputations performed at Toowoomba Hospital during an 18-year period were retrospectively reviewed. Mortality data were obtained from the Queensland Registry of Births, Deaths and Marriages. Kaplan–Meier analysis was performed to determine survival after amputation. Results: A total of 147 patients were included in the study, with 104 undergoing below knee and 43 undergoing above knee amputations. Ten patients identified as having an Aboriginal and Torres Strait Islander background. For all patients, the 30-day mortality was 4.1% and 1-year mortality was 21.1%. For Indigenous patients, 30-day mortality was 10%. Previous minor amputation had occurred in 40 patients. Twenty-nine patients underwent further minor surgery after their initial major amputation, with thirteen requiring subsequent major amputation. Factors that increased mortality risk were the presence of peripheral vascular disease, an American Society of Anesthesiologists score of four and age greater than 65 years. Conclusion: The morbidity and mortality following major lower limb amputation is significant. The findings of this study highlight the importance of preventative measures to minimize the incidence of lower limb amputations in the future.